SYSTEM OF DISTRIBUTION CHANNELS PRODUCTS DRINKING WATER THE PACKING (DWTP) UHAMQUA IN THE BUSINESS DIVISION UHAMKA JAKARTA UNIVERSITY OF MUHAMMADIYAH PROF. DR. HAMKA, 2016 - Latief, Abdul Madjid; Sari, Shinta Purnama (Prosiding Seminar Nasional Berseri, 2017)
This study aims to determine how the selection of distribution channels used by the division UHAMKA effort in marketing their products so that the product reaches the konsumenya cepar, and how the functions in the distribution channel that is carried out by the business divisionsUHAMKA. The number of informants of this study were 3 people consisting of director, secretary and financial staff UHAMKA business division, to three informants are people who know and are experts in distribution channels. The method used is descriptive qualitative. The research sample using purposive sampling. Based on the results of the study, that the selection of distribution channels used is the distribution channel of direct and indirect distribution channels where theÂ  business divisions UHAMKA not only market its products directly to consumers and but also to market through an intermediary, such intermediaries ie schools muhammadiyah jabodetabek already have cooperation with the business divisions UHAMKA, and for the functions performed by the distribution channels UHAMKA business divisions run, profesioanal and in accordance with procedures.